A family of quantum graph vertex couplings interpolating between different symmetries. (7th June 2018) - Exner, Pavel; Turek, Ondřej; Tater, Miloš
Abstract: The paper discusses quantum graphs with a vertex coupling which interpolates between the common one of the δ type and a coupling introduced recently by two of the authors which exhibits a preferred orientation. Describing the interpolation family in terms of circulant matrices, we analyze the spectral and scattering property of such vertices, and investigate the band spectrum of the corresponding square lattice graph.